ANALISIS DAMPAK PANDEMI COVID-19 TERHADAP HARGA SAHAM SEKTOR PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Maya Febrianty Lautania; Dinaroe Dinaroe; Linda Linda (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2021)
This study aims to determine the impact of the COVID-19 pandemic on banking stock prices listed on the Indonesia Stock Exchange. Four banks were the sample that had the largest market capitalization in 2020, namely PT. Bank Central Asia tbk. (BBCA), PT. Bank Rakyat Indonesia (BBRI), PT. Bank Mandiri (BMRI) and PT. Bank Negara Indonesia (BBNI). The average share price announced 30 days before the first COVID-19 case was compared with the stock price after the announcement. The daily stock price used was at the closing rate. The results indicate that there is a significant decline in banking stock prices. BBNI shares experienced the largest depreciation in 30 days after the first case of COVID-19 occurred, which was -36.44%, followed by BMRI -28.52%; BBRI -27.74%, and BBCA -17.12%. This study shows that BBCA shares have a higher level of resistance to the COVID-19 than the other three stocks